Examination of the Service Quality Perception in Private and Public Sports Centers (Konya Example) - Selçuk Buğdaycı (Türk Spor ve Egzersiz Dergisi)
This is a descriptive research study, which was conducted to evaluate the perceptions and expectations of the members of sports centers concerning the service quality in the private or public sports centers. The universe of the study is comprised of individuals, who were members of private or public sports centers within the borders of Konya province. The sample group is comprised of 365 individuals from private and 371 individuals from public sports centers. Service Quality Assessment Scale was used as the data collection tool, which was developed by Lam (2000) and adapted into Turkish by Gürbüz et al. (2005). The data obtained from the scales were coded into computer environment, and statistical analyses were conducted via SPSS 22.00 program.  As the conclusion, it was observed that the service quality perceptions of the research group concerning both private and public sports centers were negative. It was also determined that the service quality scores were negative in all of the subdimensions. In the comparison of the both types of the centers, it was determined that the service quality scores perceived in the private sports centers were higher.